1996
DOI: 10.3758/bf03214550
|View full text |Cite
|
Sign up to set email alerts
|

Response conformity in recognition testing

Abstract: In a recognition memory test for ajust-studied word list, subjects responded positively or negatively to each test word in the presence of another subject, with the two taking turns to call out their responses. Responses given second tended to conform to those given first. This was so for responses to both targets and lures and following both positive and negative first responses, although the effect was sharply reduced for targets given a negative first response. The same pattern of results was obtained in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 9 publications
10
106
0
3
Order By: Relevance
“…In other words, from the recognition performance results we may suspect that participants rely on external sources because it benefits their performance (see also Reysen, 2005;Schneider & Watkins, 1996). We cannot be sure, however, whether 'don't know' responses are used to regulate the accuracy of a memory report in this scenario, because we do not have access to responses participants decided to withhold by answering 'don't know'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, from the recognition performance results we may suspect that participants rely on external sources because it benefits their performance (see also Reysen, 2005;Schneider & Watkins, 1996). We cannot be sure, however, whether 'don't know' responses are used to regulate the accuracy of a memory report in this scenario, because we do not have access to responses participants decided to withhold by answering 'don't know'.…”
Section: Discussionmentioning
confidence: 99%
“…If it is assumed that evidence from external cues joins internally-generated memorial evidence in the overall pool of evidence, then in the state of subjective uncertainty, MEMORY, METAMEMORY, AND SOCIAL CUES 10 when little or no internal evidence is available, external evidence may become a dominant basis for memory and metamemory decisions. Indeed, in a few studies that looked directly at confidence in the context of memory conformity, it was found that confidence is indeed affected by cues provided by external sources (Jaeger, Cox, & Dobbins, 2012;Schneider & Watkins, 1996). Given that response withholding is almost invariably related to confidence (Koriat & Goldsmith, 1996), this allows for a prediction that conditions inducing memory conformity should also induce metamemory conformity.…”
mentioning
confidence: 99%
“…First, pairs of participants are shown stimuli (e.g., pictures, words) and then tested on these together (Schneider & Watkins, 1996). The participants in these studies typically answer between 50 to 100 memory questions, so the number of data points for each participant makes this design powerful.…”
Section: Memory Conformity Methodologymentioning
confidence: 99%
“…Importantly, these studies found that there was a social component in misremembering erroneous details. Schneider and Watkins (1996) Misinformation provided by the first person lowered the hit rate (correcting identifying an old word as old) by 10% and raised the false alarm rate (incorrectly identifying an old word as new) by 20%. The Schneider and Watkins (1996) study inspired other researchers to investigate why this phenomenon occurred.…”
Section: Social Influence On Memorymentioning
confidence: 99%
See 1 more Smart Citation